2011
DOI: 10.1121/1.3625257
|View full text |Cite
|
Sign up to set email alerts
|

Passive acoustic survey of Yangtze finless porpoises using a cargo ship as a moving platform

Abstract: In order to periodically investigate the population and distribution of the Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis) in its main distribution range in the Yangtze River, a passive acoustic system deployed on a cargo ship as a moving platform, rather than a dedicated research ship, was developed. A stereo acoustic event data-logger (A-tag) was installed on the cargo ship to passively detect phonating animals. In three surveys carried out in the Yangtze River from Wuhan to Shanghai,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Yangtze River (Zhao et al ; Dong et al ). The average distance between two port areas was 85.5 ± 45.5 km, with minimum and maximum distances of 27 and 157 km, respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yangtze River (Zhao et al ; Dong et al ). The average distance between two port areas was 85.5 ± 45.5 km, with minimum and maximum distances of 27 and 157 km, respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The discriminating parameters included the minimum number of pulses in a click train, the maximum duration of ICIs between two pulses, and the differences in ICI and SPL between two pulses. Because porpoise sonar always exhibits pulse trains (Au ), the minimum number of pulses in a click train was conservatively set at 5 (Dong et al ; Sasaki‐Yamamoto et al ). Successive clicks were considered as one click train if the ICI was shorter than 200 ms (Akamatsu et al ), because 90% of ICIs were smaller than 276 ms and the occurrence of ICIs near 200 ms was almost negligible in both free‐ranging and tagged finless porpoises (Akamatsu et al ; Akamatsu et al ).…”
Section: Methodsmentioning
confidence: 99%
“…This width was similar to the Yangtze River system; the average width in most regions of the Yangtze River was less than 2 km (Dong et al . ). In addition, the distribution patterns of porpoises with respect to the transect line in both the Yangtze River and Poyang Lake were approximately the same; over 80% of the porpoises were observed in near‐bank areas rather than in mid‐channel areas (Xiao and Zhang , Wei et al .…”
Section: Discussionmentioning
confidence: 97%
“…) or deploying the A‐tag at the side of a cargo ship (Dong et al . ) to detect the sonar sound of the porpoises. This protocol has also been used at the junction of Poyang Lake and the Yangtze River to reveal the seasonal distribution of the local porpoise population (Kimura et al .…”
mentioning
confidence: 99%
“…Those few studies carried out in confined coastal and inland waterways that are found in the literature have focused on a variety of issues, including acoustic scintillation to estimate current flow (Di Iorio and Farmer, 1994), active sonar systems for biological stock assessment and fisheries management (Xie, 2000), homeland security applications (Stolkin et al, 2006), acoustical communication (van Walree et al, 2007, acoustical monitoring of tidal bores (Zhu et al, 2010), marine mammal surveys (Dong et al, 2011), seasonal trends in a large remote fjord (McConnell et al, 1992), recreational boat noise in waterways (Haviland-Howell et al, 2007), ambient noise in freshwater habitats (Wysocki et al, 2007), high-frequency noise spectra in shallow brackish water (Poikonen, 2010), long-term noise trends in large, industrialized rivers (Vracar and Mijic, 2011), acoustical monitoring of ship traffic (Fillinger et al, 2011), acoustic attenuation properties in a river (Roh et al, 2008), sitespecific acoustic propagation models for the lower Hudson River Estuary (Radhakrishnan, 2009), and acoustic quantification of stratified turbulence in the Connecticut River (Lavery et al, 2013).…”
mentioning
confidence: 99%